Kajian Feminisme dalam Novel Sekar Karya Aqiladyna - Hanifa Zahra; Sri Rahayu (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Feminism is a form of resistance to patriarchal ideology in which women are inferior to men. Feminism aims to raise awareness and fight against the exploitation of women in society. The purpose of this study was to obtain data and information to describe, analyze, and interpret data on social aspects of feminism based on the process of socialization, social tasks, and social class in Aqiladyna's novel Sekar. The main theory used by the author is the theory of Sikana (2005). The approach used is a qualitative approach with the type of library research. The method used is descriptive method. The data collection technique used is hermeneutic technique. The data analysis technique used by the author is content analysis technique. The results of the feminist analysis research in Aqiladyna's novel Sekar contained 16 data consisting of (5) data on the socialization process, (5) data on social tasks, and (6) data on social class. The social aspect in the novel Sekar by Aqiladyna describes the social injustice experienced by women, especially in the Sekar character which can be seen from the process of socialization, social tasks, and social class.